Financial leverage and debt maturity targeting: International evidence - Ali Gungoraydinoglu; Özde Öztekin (Journal of Risk and Financial Management, 2021)
We provide evidence on leverage and debt maturity targeting in a large international setting. There are key differences in the relative importance of institutional factors in explaining actual as opposed to target capital structures. Targets and target deviations are plausibly influenced by the institutional environment. Firms from countries with strong legal institutions target lower leverage and higher long-term debt, whereas better-functioning financial systems result in lower target leverage and long-term debt. Financial crisis has shifted the desired structure of the securities toward shorter maturities and has led to more prevalent target deviations. Better institutions significantly decrease the likelihood of target deviations.
Keywords: G20; G32; 330; institutions; debt maturity; international; target capital structure